Systematic Review of Diagnostic Methods for Fetal Hypoxia - Nurova Aliya Askarovna (Genius Journals, 2023)
Fetal hypoxia is a serious complication during pregnancy and childbirth, which leads to an increased incidence of perinatal morbidity and mortality. The main reasons leading to fetal hypoxia are acute or chronic changes in the functional system “mother-placentafetus”. Hypoxia occurs due to placental insufficiency, a process in which there is a progressive deterioration in the functioning of the placenta when the transfer of oxygen and nutrients to the fetus through the placenta is reduced, leading to decompensated hypoxia and acidosis. The article pays attention to some methods for assessing fetal hypoxia, such as dopplerometry and measuring the acid-base balance of the fetus in umbilical cord blood.
Keywords: fetal hypoxia; acid-base balance; dopplerometry; umbilical cord blood